Expression and functional characterization of glutamine synthetase from giant freshwater prawn (Macrobrachium rosenbergii) under osmotic stress. (28th June 2019) - Lu, Zhijie; Qin, Zhendong; Sarath Babu, Vijayaraman; Ye, Chengkai; Su, Guomao; Li, Jiabo; Yang, Guang; Shen, Haiyang; Pan, Gan; Lin, Li
Abstract: The freshwater prawn, Macrobrachium rosenbergii naturally lives in the freshwater, though it migrates to the brackish water environment during spawning that claimed to be resistant on a broad range of saline fluxes. However, little is known about the osmoregulatory patterns and the effect of an enzyme glutamine synthetase (GS) in M. rosenbergii under stress. Here, we described the identification and functional characterization of GS from M. rosenbergii ( Mr ‐GS) at molecular and protein levels. The identified Mr ‐GS was comprised of 361 amino acids that phylogenetically shared the highest identity with other crustaceans and predicted to contain Gln‐synt_C and Gln‐synt_N domains at the respective terminal regions. Tissue distribution analysis in M. rosenbergii revealed that the Mr ‐GS was highly expressed in muscle, and commonly existed in other examined tissues in the following order gills > heart > stomach > brain > haemolymph. Whereas, the mRNA of Mr ‐GS was significantly up‐regulated in the muscle and gill tissues following challenges with either hyper (0 → 13‰), or hypo (13 → 0‰) osmotic stress at 3, 6 and 12 hr. Furthermore, the level of Glutamine concentration was positively correlated with the GS mRNA and protein expression patterns in hyper‐osmotic stress, whereas in hypo‐osmotic stress a slight decrease in the gills and maintained a level in the muscle tissues at 3, 6 and 12 hr post‐treatments. Our findings suggest that Mr ‐GS potentially exhibited the osmoregulation responses in the gill and muscle tissues of M. rosenbergii throughout the time of osmotic stress, which will benefit for future study on osmoregulation.